2009
DOI: 10.1197/jamia.m2604
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Multi-typed Structurally Viewed Chemicals with the UMLS Refined Semantic Network

Abstract: The modified RSN provides an enhanced abstract view of the UMLS's chemical content. Its array of conjugate and complex types provides a more accurate model of the variety of combinations involving chemicals viewed structurally. This framework will help streamline the process of type assignments for such chemical concepts and improve user orientation to the richness of the chemical content of the UMLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Various other projects have extended ontologies and terminologies to meet different needs or for other applications. In the biomedical domain, for example, an expansion of terms relevant to muscle biology was incorporated into the Gene Ontology (GO Ontology; Feltrin et al., ); Chen, Morrey, Gu, Halper, and Perl () developed a refined UMLS semantic network to distinguish between chemical complex types and conjugates in the UMLS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various other projects have extended ontologies and terminologies to meet different needs or for other applications. In the biomedical domain, for example, an expansion of terms relevant to muscle biology was incorporated into the Gene Ontology (GO Ontology; Feltrin et al., ); Chen, Morrey, Gu, Halper, and Perl () developed a refined UMLS semantic network to distinguish between chemical complex types and conjugates in the UMLS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We are not suggesting this change for the current SN framework unless a driving need can be established. However, for the alternative network of the “Refined Semantic Network” [20, 21], this problem can be dealt with by adding special types called intersection types , similar to the treatment in [17]. …”
Section: Discussionmentioning
confidence: 99%
“…We previously performed research into the modeling of conjugate and complex types in the framework of the Refined Semantic Network (RSN) [17]. In that research, concepts with a redundant ST assignment were identified as erroneous but the resolution of those errors was not discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Ambiguity, incorrect classification, and inconsistencies were readily identified in the pure intersections that were examined. New conjugate and complex semantic types are suggested in [104] to better capture the semantics of concepts assigned multiple structurally viewed chemical semantic types. For such concepts the proper semantics expresses a chemical reaction or mixture rather than the typical conjunctive semantics of multiple semantic types.…”
Section: Auditing Methodsmentioning
confidence: 99%